Features of planning of training process in a competition period for sportsmen 13-15 years, engaged in sporting dances of ballrooms - Bachinskaya N.V; Fedoryaka A.V (Kharkov National Pedagogical University, 2010)
The features of planning of training process are examined in a competition period for young sportsmen 13-15 years. The features of planning of training process are rotined in the competition period of preparation of sportsmen. The level of physical development is certain, to physical preparedness and functional indexes of sportsmen. The averages of the trainings loadings of competition mesocycle are certain for sporting pair. On the amount of figures: large loadings - 150-155; middle - 100-120; small - 70-80. After the amount of dances: large loadings - 20 and anymore; middle - 14-18; small - 10-12.